Caernarfon castle and town walls - Taylor, A. J. (Arnold Joseph), 1911-2002; Cadw (Organization : Great Britain) (Cardiff : Cadw, 1993)
The history - Tour of the Castle - Tour of the town walls
Title from cover, p. [2].
Includes bibliographical references (p. 48).
Keywords: Caernarfon Castle (Caernarfon, Wales).; Caernarfon (Wales) -- Buildings, structures, etc; City walls -- Wales -- Caernarfon